Kepatuhan Pengendalian Intern dan Perilaku Etis Karyawan di PT. Intan Bali Cargo International - Wibawa, I Made Surya Widhi; Suryanawa, I Ketut (E-Jurnal Akuntansi; Vol 31 No 12 (2021), 2021)
PT. Intan Bali Cargo International is a company engaged in the international freight forwarding industry. This study aims to analyze the influence of the control environment, risk assessment, control activities, information & communication and monitoring to ethical behavior of employees at PT. Intan Bali Cargo International. The sample was determined using the purposive sampling method so that 47 respondents were selected as the sample. Multiple linear regression analysis technique was used to analyze the data. The results of the analysis show that the control environment, risk assessment, control activities, information and communication, and monitoring have a positive and significant effect on the ethical behavior of employees at PT. Intan Bali Cargo International. These results indicate that the higher the level of internal control compliance, the ethical behavior of employees in the company will also increase. Keywords : Control Environment; Risk Assessment; Control Activities; Information and Communication; Monitoring.